Relationship between heart rate variability and inflammation induced by physical exercise in a sedentary healthy population - Ramiro-Cortijo, David; Ruvira, Santiago; Alonso de Celada, Ricardo; Muñoz-Gómez, Elena; Cañas, Silvia; Magalhães, Jose; Arribas, Silvia M. (Frontiers in Physiology, 2025)
Heart rate variability (HRV) evaluates autonomic nervous system (ANS) function, and in disease conditions a reduction in HRV is associated with inflammation. We hypothesized an association between HRV and physical exercise-induced inflammation in healthy conditions. We aimed to evaluate the relationship between HRV and plasma cytokines before and after exercise, assessing the influence of sex. Sedentary young subjects (22 females, 16 males) underwent HRV evaluation through a chest band, at rest and 15 min and 48 h after a step-exercise performed until exertion, assessing R-R interval, RMSSD, low, high frequencies (LF, HF) and total power (TP). Capillary blood was obtained before and post-exercise (2 h and 48 h), assessing plasma IL-1α, IL-1β, IL-6, IL-12, MCP-1, TNFα, IL-1ra and IL-10 with multiplex ELISA. Linear regression (LRM) and additive models (GAM) were used to evaluate associations. Exercise induced LF/HF elevation (sympathetic dominance) and HF/TP reduction (parasympathetic suppression) at 15 min post-exercise, and a rise in IL-6 and IL-10 at 2 h, higher in males than in females. All measurements were normalized by 48 h. At rest, LF/HF correlated positively with IL-1β, whereas HF/TP correlated negatively with IL-1α, IL-1β, and IL-1ra; these associations persisted 15 min post-exercise, with an additional negative correlation between HF/TP and IL-12. LRM indicated a trend for an inverse relationship between HF/TP at rest and IL-1α at 2 h, and GAM revealed a nonlinear association between LF/HF at rest and IL-1β at 2 h. At 15 min post-exercise, LF/HF further associated with IL-1β and IL-12. These findings suggest that greater parasympathetic activation at rest and post-exercise may be linked to lower exercise-induced pro-inflammatory cytokines. Further research in other cohorts is warranted to confirm the capacity of HRV as indicator of inflammation in sport.